Social Responsibility in Media: Utopia or Reality? Some actions to achieve a fine management - Ramírez Lozano, Julianna (2012)
The importance of Social Responsibility in Media is an issue that is in constant debate inside and outside Media. This concern about the impact of the information they diffuse to their public. As it is widely known, they have a strong influence in the Public Opinion on citizenship. In other words, the media has to be responsible not only for the information but also for the opinion they offer.